Filial relationship between Jose Marti and his mother through correspondence - Lázaro Javier Hernández-Bridón; Javier Gonzalez-Argote; Rafaela Ambrosio-Borroto (Universidad Médica Pinareña, 2021)
Introduction: nothing better to know a man of public life than his correspondence, undoubtedly the most sincere and intimate legacy. His letters reveal the life-work coherence of the apostle and provide important elements to detail the circumstances in which he revolutionized.